The Cimidae and Pyramidellidae (Cingulininae, Chrysallidinae, Turbonillinae) (Gastropoda) of the Miocene Central Paratethys Sea - Harzhauser, Mathias; Micali, Pasquale; Landau, Bernard M. (Zootaxa, 2026)
We present a critical evaluation of the Cimidae and of the Pyramidellidae subfamilies Cingulininae, Chrysallidinae and Turbonillinae from the Miocene of the Central Paratethys Sea. With 120 species, the assemblages were surprisingly diverse and genera, such as Chemnitzia, Parthenina, Pyrgulina and Pyrgostylus experienced major phases of radiations during the Middle Miocene. About 45% of the species described are new to science, documenting that the small-shelled fauna of the Central Paratethys Sea is still largely unknown. Consequently, the rate of endemism is extraordinarily high, which is most probably a result of the poor state of knowledge of coeval pyramidellid faunas of the Proto-Mediterranean Sea rather than a true biogeographic pattern. In total, 57 species are described as new species from the Paratethys: Graphis tisiphone sp. nov., Cingulina erebos sp. nov., Parthenina alkyone sp. nov., Parthenina beroe sp. nov., Parthenina dodona sp. nov., Parthenina eidyia sp. nov., Parthenina erato sp. nov., Parthenina keto sp. nov., Parthenina nofronii sp. nov., Parthenina sagaritis sp. nov., Parthenina steini sp. nov., Parthenina thalia sp. nov., Pyrgulina alekto sp. nov., Pyrgulina hesione sp. nov., Pyrgulina moira sp. nov., Trabecula terpsichore sp. nov., Tragula euphrosyne sp. nov., Aglaianilla aglaia sp. nov., Aglaianilla auxo sp. nov., Hesychianola hesychia sp. nov., Metisnilla metis sp. nov., Metisnilla minima sp. nov., Mormula kyma sp. nov., Pyrgiscus ananke sp. nov., Pyrgiscus karya sp. nov., Pyrgiscus pasiphe sp. nov., Pyrgostylus adarsteia sp. nov., Pyrgostylus asterope sp. nov., Pyrgostylus lachesis sp. nov., Strioturbonilla orea sp. nov., Sulcoturbonilla oizys sp. nov., Chemnitzia dione sp. nov., Chemnitzia kelaino sp. nov., Chemnitzia merope sp. nov., Chemnitzia nephele sp. nov., Chemnitzia phaio sp. nov., Chemnitzia pleione sp. nov., Chemnitzia polyxo sp. nov., Chemnitzia taygete sp. nov., Euterpenilla eurynome sp. nov., Euterpenilla euterpe sp. nov., Paraturbonilla pliocaenica sp. nov., Turbonilla alkmene sp. nov., Turbonilla anaxo sp. nov., Turbonilla andromeda sp. nov., Turbonilla chariklo nov. sp Turbonilla cymadoce sp. nov., Turbonilla deiopea sp. nov., Turbonilla echo sp. nov., Turbonilla galaxaule sp. nov., Turbonilla harmonia sp. nov., Turbonilla kalypso sp. nov., Turbonilla koryphe sp. nov., Turbonilla lilaia sp. nov., Turbonilla ozomene sp. nov., Turbonilla pherusa sp. nov. and Turbonilla ptelea sp. nov. Paraturbonilla pliocaenica sp. nov. is described from the Pliocene of Estepona (Spain). Hesychianola gen. nov. is introduced as new genus within Chrysallidinae. Aglaianilla gen. nov., Asmundanilla gen. nov., Euterpenilla gen. nov., Metisnilla gen. nov. and Parapyrgiscus gen. nov. are introduced as new genera within Turbonillinae.